2021
DOI: 10.1088/1742-6596/1720/1/012011
|View full text |Cite
|
Sign up to set email alerts
|

Development of Learning Media Using Android-Based Articulate Storyline Software for Teaching Algebra in Junior High School

Abstract: Mathematics is a science that deals with the study of abstract forms so that it requires objects or visual aids to concretize them to become more tangible and clear. Science and technology has developed rapidly in education, one of which is an android-based learning media. The purpose of this study was to develop an Android-based learning media on mathematics specifically in the form of algebraic for students in grade VII of SMP Negeri 2 Kartasura. Furthermore, after the development, the validity and feasibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 5 publications
0
3
0
1
Order By: Relevance
“…These results are in line with the results of previous research. Articulate Storyline-based learning media can facilitate the implementation of the learning process and create an interesting learning atmosphere so that learning is high quality and takes place optimally (Nissa et al, 2021;Nugroho & Arrosyad, 2020). Local wisdom values are also supported by students' interest in the learning process, which is integrated into the learning media.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in line with the results of previous research. Articulate Storyline-based learning media can facilitate the implementation of the learning process and create an interesting learning atmosphere so that learning is high quality and takes place optimally (Nissa et al, 2021;Nugroho & Arrosyad, 2020). Local wisdom values are also supported by students' interest in the learning process, which is integrated into the learning media.…”
Section: Discussionmentioning
confidence: 99%
“…Articulate Storyline media is proven to increase students' interest in learning through learning activities and can be used as a supporting medium for teachers in delivering learning materials (Oktaviana et al, 2020;Sari & Harjono, 2021). Besides being able to be used as a learning medium for addition material in lower grades, it can also be used for some characteristics of mathematics learning materials such as algebra and function graphs (Nissa et al, 2021;Pratama, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this research seeks to enhance teachers' knowledge and understanding of effective learning media by showcasing the potential and benefits of Articulate Storyline. By building upon the findings of previous studies, this research contributes to the advancement of instructional design and promotes the adoption of innovative and interactive approaches in educational settings; some relevant studies can be found (Ariani, 2020;Hadza et al, 2020;Istyadji et al, 2022;Jubaerudin et al, 2021;Nasution & Darwis, 2021;Nissa et al, 2021;Nugroho & Arrosyad, 2020;Rianto, 2020;Saadah et al, 2022;Yolanda et al, 2022).…”
Section: Introductionmentioning
confidence: 92%